EIF Private Debt Survey 2021: ESG considerations in the lending strategy of private debt funds - Helmut Krämer-Eis; Jörn Block; Antonia Botsari; Lena Benz; Salome Gvetadze; Carlos Krause; Alexandra Moritz; Frank Lang; Anna Schulze (European Investment Fund (EIF), 2022)
Against the background of the need for alternative and additional financing channels for SMEs in Europe, this paper analyses the market segment of debt funds and provides comprehensive insight into ESG considerations in the lending strategy of private debt funds. The paper is based on the results of the EIF Private Debt Survey, a new study that provides unique perspective and helps increase the transparency of the market to the public. More specifically, the paper addresses the following questions: What motivates PD fund managers' ESG engagement? What are the most common ESG strategies? How do PD fund managers implement ESG criteria in terms of policies and procedures? What are the biggest challenges they face? Do they consider gender diversity?
Keywords: 330